Analysis of Publication Trends, Interaction of Causal Factors, and Traffic Safety Intervention Strategies: Case Studies and Methodology from 2017 to 2024 - Sanjay, Krishna Tri; Suhardi, Bambang; Yuniaristanto, Yuniaristanto (Proceedings of the International Conference on Green Technology, 2026)
The increasing use of vehicles due to urbanization and technological advances increases the risk of traffic accidents, with significant social and economic impacts. Data from Indonesia shows more than 100,000 accident cases in 2023, causing losses of up to IDR 50 trillion per year. This study aims to explore several important aspects related to road traffic accidents. First, how do publication trends from 2017 to 2024 affect sustainable transport research and policy, highlighting the contribution of key journals and the role of productive countries in publication? Second, how do interactions between driver behavior, road conditions, and vehicles affect the risk and severity of road traffic accidents, and how can the Health Belief Model be used to understand driver behavior in the context of road safety? Finally, how can factor mapping of each article related to transportation mode, methodology, scientific contribution, and clustering of weaknesses of findings help design study dominance factors, identify weaknesses in current research, and provide a basis for further study development in the field of road traffic accidents. The search strategy for road traffic accident studies involved using the Scopus database  from 2017-2024, resulting in 5,035 documents. After filtering duplicates and irrelevant records, 35 studies met the inclusion criteria. Data were collected and analyzed to understand the causal factors of road traffic accidents. The Health Belief Model is important for traffic safety interventions with a focus on risk perception. The contribution of this research is as input for stakeholders in developing regulations in the field of transportation safety.